New ICT sectors: Platforms for European growth? - Reinhilde Veugelers (Bruegel, 2012)
Europe's failure to specialise in new ICT sectors and firms is likely to hold back Europe's post-crisis recovery. Europe lacks in particular leading platform providers, who are capturing most of the value in the new ICT ecosystem. In-depth analysis of some specific new emerging ICT sectors shows that the problem in Europe appears not to be so much in the generation of new ideas, but rather in bringing ideas successfully to market. Among the barriers are the lack of a single digital market, fragmented intellectual property regimes, lack of an entrepreneurial culture, limited access to risk capital and an absence of ICT clusters. The EU policy framework, particularly the Innovation Union and Digital Agenda EU 2020 Flagships, could better leverage the growth power for Europe of new ICT markets. The emphasis should move beyond providing support for infrastructure and research, to funding programmes for pre-commercial projects. But perhaps most important is dealing with the fragmentation in European digital markets.
Keywords: 330; IKT-Sektor; Internetportal; Internetbasierter Dienst; Telekommunikationspolitik; Innovationspolitik; Immaterialgüterrechte; EU-Staaten